Overconfidence in SMEs Conceptualisations, Domains and Applications - Invernizzi, Anna (Springer International Publishing, 2018)
This book presents a review of the role of overconfidence in small firms and explores how biased judgment and decision-making can affect business performance. Whilst the overconfidence construct has been studied in detail, there are no systematic reviews of its role in SMEs as of yet. Examining the decisions made by entrepreneurs, this study offers clear solutions on how to improve business accuracy, reduce disadvantageous investments and prevent bankruptcy. Providing an empirical analysis of overconfidence in the sport industry, this new book will not only be of interest to academics of entrepreneurship and small enterprises, but also to sport managers.